The knowledge, awareness and practices of DBM-VI employees on electronic commerce - Matutino, Warren R. (2006)
This study sought to determine the knowledge, awareness and practices of DBM-VI employees on e-commerce. The respondents were 24 regular employees of the Department of Budget and Management Regional Office VI for the period 2005-2006. The research instrument was a survey questionnaire that was developed on the basis of the problems identified. The data culled from the questionnaires were presented in frequency distribution tables using frequency counts and percentages. significant differences in means were analyzed using the one-way analysis of variance (ANOVA) at five percent alpha level of significance. This study showed that: (1) with respect to knowledge on e-commerce, the grand mean of the respondents is 2.63 or equivalent to an adjectival rating of extensive; (2) in terms of awareness, the grand mean of 2.60 can be interpreted as "agree" which means that, on the whole, the employees agree on the advantages and disadvantages of e-commerce and (3) with regards to practices, several insights can be gleaned such as (a) the computer was the most common technological devise used by the respondents, (b) computers were always used, (c) a majority se e-commerce technologies in shopping and (d) mobile phones were used almost daily. The statistical analysis revealed that the knowledge and awareness of the respondents on e-commerce vary significantly with respect to the various socio-economic factors such as gender, age, civil status, religion, education, salary and income. On the other hand, the ANOVA on practices of respondents showed varying results. These findings confirmed that employees at DBM-VI have extensive knowledge on e-commerce. Their capabilities reflect their recognition of the benefits and risk arising from this technology.
Research Paper (Mgt 299-Research Methods in Management). -- Iloilo City : UPV-CM, February 2006.